A review of the production process of bacteria-based polymeric flocculants. (April 2021) - Abu Bakar, Siti Nur Hatika; Abu Hasan, Hassimi; Abdullah, Siti Rozaimah Sheikh; Kasan, Nor Azman; Muhamad, Mohd Hafizuddin; Kurniawan, Setyo Budi
Graphical abstract: Highlights: Bio-based polymeric flocculants as an alternative to chemical and grafted flocculants. The process of bio-based polymeric flocculant production by bacteria was explained. Extraction and purification methods were discussed. Scaling-up challenges of bio-based polymeric flocculant production were discussed. Abstract: The utilisation of chemical flocculants in water and wastewater treatment has drawn several concerns especially in terms of further toxicity and its effect to the environment. The utilisation of chemical flocculants produces non-biodegradable and hazardous sludge as by-product of the treatment. Bioflocculants are observed as an alternative to chemical flocculants due to their comparable efficiencies. They are biodegradable, eco-friendly, and safe to handle. The identification and production of novel bioflocculants has gained much attention worldwide and extensively reported. Amongst all, bacteria receive the most attention because of its availability and ability to produce bioflocculants with many specialties. This review paper summarises the extraction and purification processes in bioflocculant production as vital aspect that determine the production yield, which is currently still scattered. Solvent extraction, ultrasound-assisted extraction, hydrothermal, microwave-assisted, and enzyme-assisted are examples of extraction techniques, while lyophilisation, ion-exchange and dialysis are the purification techniques often adopted in bioflocculant production. This review paper also provides brief introduction on plant-, crustacean-, and microorganism-based bioflocculant as promising compounds with high flocculating activity. The development of bioflocculants is representing important progress in sustainable environmental technology. The need to provide a selection of inexpensive, promising extraction, and purification techniques for bioflocculant production are the challenges for bioflocculant production and future research directions on this subject should be emphasized to be applied further in water and wastewater treatment.